Improvement of Freezing of Gait in Patients with Parkinson's Disease by Imagining Bicycling - Akio Kikuchi; Toru Baba; Takafumi Hasegawa; Naoto Sugeno; Masatoshi Konno; Emiko Miura; Ryuji Oshima; Masashi Aoki; Atsushi Takeda (Case Reports in Neurology, 2014)
Freezing of gait (FOG) is one of the factors that reduce the quality of life in patients with Parkinson's disease (PD). Imagining bicycling before gait start provided improvement in FOG in 2 PD patients. Imagining and mimicking bicycling after the initiation of gait allowed the rhythmic gait to continue without interruption. We suggest that imagining and mimicking bicycling, which are nonexternal cues, could serve as a helpful therapeutic approach for the intractable freezing and interruption of gait of PD patients.